PP.04.08: LEFT VENTRICLE HYPERTROPHY IN PATIENTS WITH NEW DIAGNOSED HYPERTENSION. (June 2015) - Koncarevic, I.; Zdravkovic, M.; Krotin, M.; Hinic, S.; Lisulov-Popovic, D.; Gavrilovic, J.; Klasnja, S.; Acimovic, T.; Dimkovic, S.; Saric, J.; Lovic, D.
Abstract : Objective: Left ventricular hypertrophy (LVH) is a structural remodeling of the heart developing as a response to volume and/or pressure overload. Previous studies have shown that in patients with long duration of hypertension, hypertension is not an independent factor in the development of LVH and occurrence does not depend on the length and severity of hypertension, but the role played by other comorbidities such as triglycerides, age, gender, genetics, insulin resistance, obesity, physical inactivity, increased salt intake and chronic stress. To evaluate incidence of LVH in patients with newly diagnosed hypertension and to define combined risk factors for LVH in newly diagnosed hypertensive patients. Design and method: 126 consecutive patients. with newly diagnosed hypertension were enrolled in the study. Echocardiography was done in all of them within the first month following the diagnosis. LVH was defined according to the latest ESH guidelines for hypertension management suggest that LVMI above 115 g/m2 for men, and 95 g/m2 for women determine LVH. In all patients we determined BMI, cholesterol and tryglicerides level. Results: LVH was diagnosed in 33 patients (26.2 %). There was no significant difference in arterial tension measured during the first physical examination between patients with and without LVH (156+/−92 mmHg vs 152 +/− 93 mmHg, p = 0.089). There was higher incidence in females compared to males (21 or 63, 3% vs 12 or 36, 7 %) p < 0.001. Patients with LVH had significantly higher BMI (24.6 +/ −2.4 vs 28.5 +/- 2.9), triglycerides (1.7+/−0.35 vs 1.9+/−0.49, p < 0.05) cholesterol (6.2+/−0.8 vs 6.9 +/- 1.1 mmol/l, p < 0.001) and they were highly significantly older (48+/−7 yrs. vs 54+/−6 years, p < 0.001) compared to patients without LVH. Conclusions: LVH is present in high proportion in patients with newly diagnosed hypertension in Belgrade region. Other cardiovascular risk factors as BMI, pathological lipodogram and age are strongly associated with the LVH in our population. Therefore these risk factors should be promptly eliminated in hypertensive patients besides antihypertensive therapy.